Strnjeni razvoj - ranljivost urbanega? - Lobnik, Uroš (Urbani izziv, 2002)
Spatial planning professions should establish and formalise inter-disciplinarybalanced models for evaluation and planning spatial development with common directions and goals. In the opposite case, urban development in Slovenia will still be evaluated from a defensive position and remain subordinate. It would be beneficial to research, how and to what extentcan sectorian and disconnected dealings with space affect the concept ofcompact city and the possibility for protecting natural and cultural landscapes. Urbanists should focus on two aspects: how to act if the interdisciplinary sustainable model will not be developed, or not at all, and to what extent to improve efficiency? The solution probably lies in the answer, why don't urban planners have the right to manage complex built-up space. Probably because their operative tools are almost completely useless inthe new social condition.
Keywords: Maribor; mesta; prostorski razvoj; prostorsko planiranje; spatial planning; urbani razvoj; urbanism; urbanizem